Early Deletion of Neurod1 Alters Neuronal Lineage Potential and Diminishes Neurogenesis in the Inner Ear - Filova, Iva; Bohuslavova, Romana; Tavakoli, Mitra; Yamoah, Ebenezer N.; Fritzsch, Bernd; Pavlinkova, Gabriela (Frontiers in Cell and Developmental Biology, 2022)
Neuronal development in the inner ear is initiated by expression of the proneural basic Helix-Loop-Helix (bHLH) transcription factor Neurogenin1 that specifies neuronal precursors in the otocyst. The initial specification of the neuroblasts within the otic epithelium is followed by the expression of an additional bHLH factor, Neurod1. Although NEUROD1 is essential for inner ear neuronal development, the different aspects of the temporal and spatial requirements of NEUROD1 for the inner ear and, mainly, for auditory neuron development are not fully understood. In this study, using Foxg1Cre for the early elimination of Neurod1 in the mouse otocyst, we showed that Neurod1 deletion results in a massive reduction of differentiating neurons in the otic ganglion at E10.5, and in the diminished vestibular and rudimental spiral ganglia at E13.5. Attenuated neuronal development was associated with reduced and disorganized sensory epithelia, formation of ectopic hair cells, and the shortened cochlea in the inner ear. Central projections of inner ear neurons with conditional Neurod1 deletion are reduced, unsegregated, disorganized, and interconnecting the vestibular and auditory systems. In line with decreased afferent input from auditory neurons, the volume of cochlear nuclei was reduced by 60% in Neurod1 mutant mice. Finally, our data demonstrate that early elimination of Neurod1 affects the neuronal lineage potential and alters the generation of inner ear neurons and cochlear afferents with a profound effect on the first auditory nuclei, the cochlear nuclei.